(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Quinolines compounds are toxic pollutants. Their biodegradation by microbes represents a tool for bioremediation. The growth of Klebsiella penumoniae on 2-methylquinoline shows typical sigmoidal bacterial growth curves. Since there exists a variety of models for describing the growth profile of microorganism such as logistic, Gompertz, Richards, Schnute, Baranyi- Roberts, Von Bertalanffy, Buchanan three-phase and more recently Huang models, the growth curves exhibit under such conditions would be an excellent study for finding the best model. The Huang model was chosen as the best model based on statistical tests such as root-meansquare error (RMSE), adjusted coefficient of determination (R2), bias factor (BF), accuracy factor (AF) and corrected AICc (Akaike Information Criterion). Novel constants obtained from the modelling exercise would be used for further secondary modelling.